Rogue justice : a thriller - Abrams, Stacey (Doubleday, 2023)
"Avery Keene is back, trying to get her feet on solid ground after unraveling a conspiracy that took down the President of the United States. But as the sparks of impeachment hearings and political skirmishes swirl around her, Avery is approached at a legal conference by Preston Davies, an unassuming young man and fellow law clerk to a federal judge in Idaho. Davies believes his boss, Judge Francesca Whitner, was being blackmailed in the days before she recently took her own life, and he gives Avery a file, a burner phone, and a fearful warning that there are highly dangerous people involved. Moments later, Avery is shocked when she witnesses Davies being murdered. After breaking the encrypted file Davies gave to her, Avery reveals a list of names-all federal judges-and, alarmingly, all judges on the FISA Court (the United States Foreign Intelligence Surveillance Court), also known as America's "secret court." It is this body that grants permission to the government to wiretap American individuals or corporations suspected of terrorism. Avery knows Judge Whitner had been extorted, but as she investigates the names and cases associated with other judges on the list she begins to see a frightening pattern-and she worries that something far more sinister may be unfolding. Drawing from today's headlines and weaving them together with her unique insider perspective, Stacey Abrams combines twisting plotlines, wry wit, and clever puzzles to create another immensely entertaining suspense novel"--